Magnetic reconnection acceleration of astrophysical jets for different jet geometries*Supported by the National Natural Science Foundation of China. (April 2015) - Chen, A-Ming; Rui, Li-Ming
Abstract The acceleration mechanisms of relativistic jets are of great importance for understanding various astrophysical phenomena such as gamma-ray bursts, active galactic nuclei and microquasars. One of the most popular scenarios is that the jets are initially Poynting-flux dominated and succumb to magnetohydrodynamic instability leading to magnetic reconnections. We suggest that the reconnection timescale and efficiency could strongly depend on the geometry of the jet, which determines the length scale on which the orientations of the field lines change. In contrast to a usually-assumed conical jet, the acceleration of a collimated jet can be found to be more rapid and efficient (i.e. a much more highly saturated Lorentz factor can be reached) while the jets with lateral expansion show the opposite behavior. The shape of the jet could be formed due to the lateral squeezing on the jet by the stellar envelope of a collapsing massive star or the interaction of the jet with stellar winds.